Energy-Efficient Opportunistic Transmission Scheduling for Sparse Sensor Networks with Mobile Relays. (3rd May 2016) - Liu, Wei; Zhao, Xiaojie; An, Yuan; Dai, Xiangjun; Ma, Qingtian; Guo, Hongjian
Abstract : Wireless sensing devices have been widely used in civilian and military applications over the past decade. In some application scenarios, the sensors are sparsely deployed in the field and are costly or infeasible to have stable communication links for delivering the collected data to the destined server. A possible solution is to utilize the motion of entities that are already present in the environment to provide opportunistic relaying services for sensory data. In this paper, we design and propose a new scheduling scheme that opportunistically schedules data transmissions based on the optimal stopping theory, with a view of minimizing the energy consumption on network probes for data delivery. In fact, by exploiting the stochastic characteristics of the relay motion, we can postpone the communication up to an acceptable time deadline until the best relay is found. Simulation results validate the effectiveness of the derived optimal strategy.